2015
DOI: 10.5539/cco.v5n1p11
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer and Its Correlates: A Study of Knowledge and Preventive Behavior in Riyadh

Abstract: Background: Worldwide, the incidence of skin cancer has increased due to increased UV exposure to solar and artificial sources. In Saudi Arabia, skin cancer ranked the 9 th most common cancer for both sexes. However, it is considered to be a preventable disease. WHO has proposed several preventive methods to avoid the damaging effects of excessive exposure to UV rays including; social education and adopting positive behavioral changes. The present study aimed to evaluate the level of knowledge, attitudes and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
6
6
1
Order By: Relevance
“…In contrast, age was found to have statistically significant associations with awareness about skin cancer in other studies. 12,[20][21][22] One interesting finding was the marital status (β=0.111, p=0.025) which was a significant predictor of awareness score, also coinciding with the findings of Alamri et al 12 The mean behavior score was 8.57±5.00 with a possible maximum score of 24 which reveals a low level of sun protection behavior in agreement to the results of other studies. 15,23 The current work found that half of the participants recognized that sun block should be applied 15-30 minutes before getting exposed to the sun, and should be re-applied every 2 hours.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast, age was found to have statistically significant associations with awareness about skin cancer in other studies. 12,[20][21][22] One interesting finding was the marital status (β=0.111, p=0.025) which was a significant predictor of awareness score, also coinciding with the findings of Alamri et al 12 The mean behavior score was 8.57±5.00 with a possible maximum score of 24 which reveals a low level of sun protection behavior in agreement to the results of other studies. 15,23 The current work found that half of the participants recognized that sun block should be applied 15-30 minutes before getting exposed to the sun, and should be re-applied every 2 hours.…”
Section: Discussionsupporting
confidence: 86%
“…Females represented more than half of the respondents (58.5%) which was similar to two previous studies. 12,13 According to our findings, it has been shown that medical students and health care providers at this tertiary hospital have narrow knowledge in regard to skin cancer which was collateral to the conclusion of previous studies conducted among the general population in Saudi Arabia, Medical students in France, Nursing students and by the American Academy of Dermatology in 1995. 12,[14][15][16] In contrast, skin cancer knowledge and perceived severity to sun exposure were shown to be high in a study in Italy among school students.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A study conducted in Riyadh, Saudi Arabia, showed that the population had a good general awareness of skin cancer but little awareness of specific details of the disease, with 83% stating they were unaware that sun exposure causes skin cancer [23]. However, a later study in Jeddah, Saudi Arabia, showed that 73% of participants were aware of the association between skin cancer and exposure to sunlight, although 58% did not know that moderate tanning also poses a risk [24].…”
Section: Introductionmentioning
confidence: 99%